2012
DOI: 10.1099/mic.0.057430-0
|View full text |Cite
|
Sign up to set email alerts
|

Inner-membrane transporters for the siderophores pyochelin in Pseudomonas aeruginosa and enantio-pyochelin in Pseudomonas fluorescens display different enantioselectivities

Abstract: Iron uptake and transcriptional regulation by the enantiomeric siderophores pyochelin (Pch) and enantio-pyochelin (EPch) of Pseudomonas aeruginosa and Pseudomonas fluorescens, respectively, are stereospecific processes. The iron-loaded forms of Pch (ferriPch) and of EPch (ferriEPch) are recognized stereospecifically (i) at the outer membrane by the siderophore receptors FptA in P. aeruginosa and FetA in P. fluorescens and (ii) in the cytoplasm by the two AraC-type regulators PchR, which are activated by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…It has since been shown that PCH has a higher affinity for Fe than previously described: 10 28.8 M −2 and 10 30.8 M −1 for PCH and PVD respectively (Albrecht-Gary et al, 1994;Brandel et al, 2012) and Fe chelation involves a stoichiometry of 1 for PVD and 2 for PCH. For the PCH pathway, the ferri-siderophore is released from the siderophore into the cytoplasm (Youard et al, 2011;Reimmann, 2012) by an unknown mechanism. The molecular mechanisms involved in iron release from siderophores in bacterial cells also differ between these two pathways (for reviews see Schalk and Guillon, 2013) and may affect the efficiency of both systems to supply P. aeruginosa cells with Fe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has since been shown that PCH has a higher affinity for Fe than previously described: 10 28.8 M −2 and 10 30.8 M −1 for PCH and PVD respectively (Albrecht-Gary et al, 1994;Brandel et al, 2012) and Fe chelation involves a stoichiometry of 1 for PVD and 2 for PCH. For the PCH pathway, the ferri-siderophore is released from the siderophore into the cytoplasm (Youard et al, 2011;Reimmann, 2012) by an unknown mechanism. The molecular mechanisms involved in iron release from siderophores in bacterial cells also differ between these two pathways (for reviews see Schalk and Guillon, 2013) and may affect the efficiency of both systems to supply P. aeruginosa cells with Fe.…”
Section: Discussionmentioning
confidence: 99%
“…Siderophore-free iron is then transported across the inner membrane by an ABC transporter (Borgna-Pignatti et al, 2006). For the PCH pathway, the ferri-siderophore is released from the siderophore into the cytoplasm (Youard et al, 2011;Reimmann, 2012) by an unknown mechanism. Moreover, PVD biosynthesis probably requires more energy than PCH biosynthesis because it involves more enzymes and precursors .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, pMMO itself houses a copper active site in the periplasmic portion of the PmoB subunit (55, 124), which is believed to be the final destination of most copper trafficked into methanotroph cells. For siderophores, demetalation can occur in the cytoplasm (e.g., pyochelin; 125) or the periplasm (e.g., pyoverdine; 117), and more work is needed to determine which is the better model for CuMbn copper release.…”
Section: Methanobactinsmentioning
confidence: 99%
“…Recently, FetF in P . protegens CHA0 was determined not to be essential for iron-E-Pch complex uptake and is proposed to be involved in E-Pch recycling [ 21 ]. In this study, we characterized the roles of these putative transporters in E-Pch production.…”
Section: Introductionmentioning
confidence: 99%